2019
DOI: 10.1186/s12943-019-1060-9
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA circ-ZKSCAN1 inhibits bladder cancer progression through miR-1178-3p/p21 axis and acts as a prognostic factor of recurrence

Abstract: Background Circular RNAs (circRNAs) represent a subclass of regulatory RNAs that have been shown to have significant regulatory roles in cancer progression. However, the biological functions of circRNAs in bladder cancer (BCa) are largely unknown. Methods Cell invasion models were established, and invasion-related circRNAs were detected by qPCR. Using above method, circ-ZKSCAN1 was picked out for further study. Circ-ZKSCAN1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 29 publications
2
95
0
Order By: Relevance
“…Circ-ITCH inhibits BC progression by sponging miR-17/miR-224 and regulating p21 and PTEN expression [9]. Studies have also found that hsa_circ_0001361 [10], circPICALM [11], hsa_circ_0137606 [12], and circ-ZKSCAN1 [13] function in BC progression. Although many circRNAs are known to have significant functions in cancer, more work is needed to confirm their impact on cancer genetics.…”
Section: Introductionmentioning
confidence: 99%
“…Circ-ITCH inhibits BC progression by sponging miR-17/miR-224 and regulating p21 and PTEN expression [9]. Studies have also found that hsa_circ_0001361 [10], circPICALM [11], hsa_circ_0137606 [12], and circ-ZKSCAN1 [13] function in BC progression. Although many circRNAs are known to have significant functions in cancer, more work is needed to confirm their impact on cancer genetics.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer (BC) belongs to the most commonly occurring malignancies of the urinary system and the ninth most frequently diagnosed cancer type with both high incidence and mortality rates worldwide 1,2 . Based on the depth of tumor infiltration, BC is categorized into muscle‐invasive bladder cancer (MIBC) (Ta, Tis, and T1, approximately accounting for 70%‐75%) and nonmuscle invasive bladder cancer (NMIBC) (T3‐T4, approximately 25%‐30%) 3‐5 . Of the patients with NMIBC, it has a higher recurrence rate after local tumor resection and is very likely to progress to MIBC 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Circ-ITCH inhibits BC progression by sponging miR-17/miR-224 and regulating p21 and PTEN expression [9]. Studies have also found that hsa_circ_0001361 [11], circPICALM [12], hsa_circ_0137606 [13], and circ-ZKSCAN1 [14] function in BC progression. Although many circRNAs are known to have signi cant functions in cancer, more work is needed to con rm their impact on cancer genetics.…”
Section: Introductionmentioning
confidence: 99%